Exome sequencing link mutation in RGPD4 with systemic sclerosis-associated interstitial lung disease and the low level of testosterone—an exploration study - Wang, Na; Zhang, Qian; Sun, Wei; Yang, Xiaoyu; Huang, Hui; Xu, Zuojun (Frontiers in Oncology, 2022)
Background: Interstitial lung disease (ILD) is the most common and potentially most devastating manifestation of SSc in pulmonary involvement. However, it is unclear about the mechanism for systemic sclerosis associated ILD(SSc-ILD). This work aims to explore the potential candidates for SSc-ILD upon the whole exome sequencing (WES) and attempts to analyze the possible pathogenesis of SSc-ILD from the perspective of the genetic level. Materials: Variants were conformed by whole exome sequencing(WES) and SKAT analysis were employed to explore the most differential variants. Targeted variants were performed in biological functions, associated with clinical manifestations, and the probable change of downstream. Results: By the WES and SKAT analysis of SSc with and without ILD, only the variants of RGPD4 achieved the statistical power (P<2.51×10-6, P-FDR=0.025, OR=15.95). A total of 20 rare functional variants(missense, truncating, splicing) were tested for RGPD4 gene, and five truncating and damaging missense variants were identified. Carriers showed the older inclusion age(P=0.02) and the higher frequency use of predinisone(P=0.02) compared to the non-carriers. Further analysis illustrated that carriers showed lower levels of TES in comparison to non-carriers but didn’t reach statistical difference(P=0.08). In bivariate correlation analysis, we analyzed the relationship between the mutant status of RGPD4 and the levels of sex hormones after adjusting for age confounders. Only the level of TES showed negative correlation with the mutant status(B=-0.509, P=0.037). Conclusion: The variants of RGPD4 might contribute to the ILD development of SSc and also might be a causative factor of lower TES among SSc-ILD, which provided the insight to a better understanding of pathobiology of SSc-ILD and androgen hormone supplement might be a therapeutic target in this debilitating disease. Keywords: RGPD4, systemic sclerosis, interstitial lung disease, rheumatoid arthritis associated interstitial lung disease, testosterone